The endoscopic ultrasound features of pancreatic fluid collections and their impact on therapeutic decisions: an interobserver agreement study - Fabbri, Carlo; Baron, Todd H.; Gibiino, Giulia; Arcidiacono, Paolo Giorgio; Binda, Cecilia; Anderloni, Andrea; Rizzatti, Gianenrico; Pérez-Miranda, Manuel; Lisotti, Andrea; Correale, Loredana; Gornals, Joan B.; Tarantino, Ilaria; Petrone, Maria Chiara; Cecinato, Paolo; Fusaroli, Pietro; Larghi, Alberto (Endoscopy, 2022)
Background A validated classification of endoscopic ultrasound (EUS) morphological characteristics and consequent therapeutic intervention(s) in pancreatic and peripancreatic fluid collections (PFCs) is lacking. We performed an interobserver agreement study among expert endosonographers assessing EUS-related PFC features and the therapeutic approaches used.Methods 50 EUS videos of PFCs were independently reviewed by 12 experts and evaluated for PFC type, percentage solid component, presence of infection, recognition of and communication with the main pancreatic duct (MPD), stent choice for drainage, and direct endoscopic necrosectomy (DEN) performance and timing. The Gwet’s AC1 coefficient was used to assess interobserver agreement.Results A moderate agreement was found for lesion type (AC1, 0.59), presence of infection (AC1, 0.41), and need for DEN (AC1, 0.50), while fair or poor agreements were stated for percentage solid component (AC1, 0.15) and MPD recognition (AC1, 0.31). Substantial agreement was rated for ability to assess PFC–MPD communication (AC1, 0.69), decision between placing a plastic versus lumen-apposing metal stent (AC1, 0.62), and timing of DEN (AC1, 0.75).Conclusions Interobserver agreement between expert endosonographers regarding morphological features of PFCs appeared suboptimal, while decisions on therapeutic approaches seemed more homogeneous. Studies to achieve standardization of the diagnostic endosonographic criteria and therapeutic approaches to PFCs are warranted.